Production of Biodiesel from Waste Vegetable Oil via KM Micromixer. (27th May 2015) - Elkady, M. F.; Zaatout, Ahmed; Balbaa, Ola
Abstract : The production of biodiesel from waste vegetable oils through its pretreatment followed by transesterification process in presence of methanol was investigated using a KM micromixer reactor. The parameters affecting biodiesel production process such as alcohol to oil molar ratio, catalyst concentration, the presence of tetrahydrofuran (THF) as a cosolvent, and the volumetric flow rates of inlet fluids were optimized. The properties of the produced biodiesel were compared with its parent waste oil through different characterization techniques. The presence of methyl ester groups at the produced biodiesel was confirmed using both the gas chromatography-mass spectrometry (GC-MS) and the infrared spectroscopy (FT-IR). Moreover, the thermal analysis of the produced biodiesel and the comparable waste oil indicated that the product after the transesterification process began to vaporize at 120°C which makes it lighter than its parent oil which started to vaporize at around 300°C. The maximum biodiesel production yield of 97% was recorded using 12 : 1 methanol to oil molar ratio in presence of both 1% NaOH and THF/methanol volume ratio 0.3 at 60 mL/h flow rate.